2016
DOI: 10.1111/emre.12074
|View full text |Cite
|
Sign up to set email alerts
|

Absorptive Capacity and Ambidexterity in R&D: Linking Technology Alliance Diversity and Firm Innovation

Abstract: The aim of this study is to examine how firms realize the benefits associated with a diverse range of technology alliances. We propose and test the hypothesis that firms’ knowledge combinative capabilities mediate the relationship between technology alliance diversity and innovation. Using panel data for Spanish manufacturing companies during the period 2004–2011, we provide evidence that firms’ absorptive capacity and ambidexterity in R&D serve as mediating mechanisms between technology alliance diversity and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 108 publications
(205 reference statements)
1
55
0
2
Order By: Relevance
“…Further research supports that knowledge creation by partners mediates the effect of knowledge acquisition on innovative performance and that international alliances strengthen the effect of knowledge creation on innovative performance [53]. Lucena & Roper [54] find that a firm's absorptive capacity and ambidexterity in R&D mediate the relationship between technology alliance diversity and innovation. Further, with regard to experience, it has been found that the general alliance experience of biotechnology partners, but not of pharmaceutical firms, positively affects joint project performance [55].…”
Section: Characteristics Of Partners Innovation Cooperation Determinmentioning
confidence: 89%
“…Further research supports that knowledge creation by partners mediates the effect of knowledge acquisition on innovative performance and that international alliances strengthen the effect of knowledge creation on innovative performance [53]. Lucena & Roper [54] find that a firm's absorptive capacity and ambidexterity in R&D mediate the relationship between technology alliance diversity and innovation. Further, with regard to experience, it has been found that the general alliance experience of biotechnology partners, but not of pharmaceutical firms, positively affects joint project performance [55].…”
Section: Characteristics Of Partners Innovation Cooperation Determinmentioning
confidence: 89%
“…Having navigated through the career path development and stayed for a long time within their companies, these managers had also been exposed to top-down/bottom-up flows of knowledge which facilitated ambidexterity enactment (Mom et al, 2009). Their explorative capabilities supporting new product/service development such as customer orientation capability (Ngo and O'Cass, 2012), combined with external relational capabilities, that is, partnerships with consultants (Rusanen et al, 2014;Lucena and Roper, 2016) provided additional knowledge support and resources for exploration. Their explorative capabilities supporting new product/service development such as customer orientation capability (Ngo and O'Cass, 2012), combined with external relational capabilities, that is, partnerships with consultants (Rusanen et al, 2014;Lucena and Roper, 2016) provided additional knowledge support and resources for exploration.…”
Section: Discussion Of the Findings And Conclusionmentioning
confidence: 99%
“…In this way, they made firms more capable of initiating various reconfigurations of resources and knowledge in the pursuits of new products/services. Their explorative capabilities supporting new product/service development such as customer orientation capability (Ngo and O'Cass, 2012), combined with external relational capabilities, that is, partnerships with consultants (Rusanen et al, 2014;Lucena and Roper, 2016) provided additional knowledge support and resources for exploration. Such exploration efforts can enhance the effects of exploitative capabilities, namely, cost efficiencies, because, through internalisation of external knowledge, exploitative capabilities in terms of efficient routines and processes can be applied on a greater scale of acquired competences (Cao et al, 2009).…”
Section: Discussion Of the Findings And Conclusionmentioning
confidence: 99%
See 2 more Smart Citations